Evaluation of lactic acid fermentation in a dairy and non-dairy beverage using two commercial starter cultures - CORREA MOSQUERA, ANA RUBY; CUENCA QUICAZAN, MARTHA MARIA (Vitae, 2022)
Background: Lactic fermentations are a catabolic process in which biochemical transformations of different organic products occur. Sugars are mainly converted into organic acids, increasing viscosity, acid taste, aroma, and flavor. Lactic acid bacteria provide probiotic characteristics if they reach counts of 106 CFU*g-1 (Colony Forming Units) in the final product, which can generate wellness for consumers. Objective: This research aimed to compare the lactic fermentation process in three substrates using two commercial cultures. Methods: Whole milk (control), aqueous extract of oats flakes, and an aqueous extract of a mixture of oats flakes with mashua pulp were used. The whole milk was heated, and the aqueous extracts were prepared. All samples were divided into two parts, keeping the temperature at 42°C, and then inoculated with Yomix y Choozit. Each fermentation lasted 6 hours at 42°C. Fermentation samples were taken each hour, and pH, titratable acidity, and Brix degrees were determined. Results: Total lactic acid bacteria were counted at the end of each fermentation. The final product was evaluated with sensory analysis. As expected, there was an increase in titratable acidity and a decreased pH and Brix degrees. It was observed that the dairy product showed the most significant changes. Fermentations performed with Yomix presented a higher count of lactic bacteria. Conclusion: It is possible to carry out lactic fermentation using substrates that do not contain milk, requiring higher initial soluble solids and a longer incubation time.